ANALISIS DANGLING MODIFIER PADA HASIL PENELITIAN DAN DISKUSI YANG DITULIS OLEH MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS UNIVERSITAS PGRI SEMARANG TAHUN AKADEMIK 2013/2014 - Ngasbun Egar; Siti Musarokah; Fitri Yulianti (Universitas PGRI Semarang, 2015)
The aims of the study are 1) to describe how dangling modifiers are used by the students in writing Research Findings and Discussion and 2) to give a solusion of the dangling modifiers produced by them. ?é?áThis study is descriptive qualitative research. The object of the study is the Final Projects, especially Research Findings and Discussion Chapter written by the English Education Department Students of University of PGRI Semarang in the academic year 2013/2014. The total number of the sample is 30 Final Projects, and purposive sampling is used in getting the sample. In collecting the data, the writers used non interactive method that is in the form of documentation. There are three components used in analyzing the data?óÔé¼ÔÇØreducing the data, presenting the data, and drawing conclusion. The result of this study shows that the writers found 39 sentences of the 22 Research Findings and Discussion indicated dangling modifier. There was no dangling modifier in 8 Research Findings and Discussion. The sentences indicated dangling modifier started with present participle, past participle, to infinitive, dan prepositional phrase. The dangling modifiers are because the inroductory phrases of the sentences did not refer to the subjects of the main clauses. In other words, the subjects of the main clauses did not match with the introductory phrases of the sentences or the parts ofmain clausewere in the form of expletive construction orpassive construction; as a result, thesubjects were not clear. In solving the problems of the dangling modifiers, the writers changed the subjects of the main clauses, so these matched with both the introductory phrases (modifiers) and the main clauses or added subordinating conjunctions and subjects (doer of action) on the introductory phrases, so these phrases became complete introductory clauses(adverbial clause). Then it is suggested for the advisors to improve the quality in guiding the students to write Research Findings and Discussion both in techniques to write them and/or the structures of the sentences, so the students can minimize the errors in writing sentences, especially dangling modifier. ?é?á Keywords: analysis,dangling modifier, Reserach Findings and Discussion